An experimental and theoretical investigation of XPS and NEXAFS of nicotine, nicotinamide, and nicotinc acid. Issue 10 (January 2020) - Sa'adeh, H; Backler, F; Wang, F; Ciavardini, A; Piccirillo, S; Coreno, M; Richter, R; Prince, K C
Synopsis: The electronic structures of nicotine, nicotinic acid and nicotinamide have been studied by valence photoemission spectroscopy (PES), core X-ray photoelectron spectroscopy (XPS), and near-edge X-ray absorp-tion fine structure (NEXAFS) and interpreted with the aid of quantum chemical calculations. Nicotinamide and nicotinic acid are closely related and show correspondingly similar spectral features, while nicotine is both structurally and spectroscopically diverse.